OP36 Individual, family and school-based interventions to prevent multiple risk behaviours in young people aged 8–25 years: a cochrane systematic review and meta-analysis. (September 2018) - MacArthur, GJ; Caldwell, DM; Redmore, J; Watkins, S; Kipping, R; White, J; Chittleborough, C; Langford, R; Er, V; Lingam, R; Pasch, K; Gunnell, DJ; et al.
Abstract : Background: We aimed to undertake a Cochrane systematic review to quantify the effect of multiple risk behaviour interventions on prevention of substance use, antisocial behaviour, sexual risk, vehicle risk, self-harm, gambling, physical inactivity and unhealthy diet among individuals aged 8–25 years as little is known about their effectiveness (CD009927). Methods: Eleven databases were searched to 14 November 2016. Randomised controlled trials were included that addressed two or more risk behaviours in individuals aged 0–18 years. Data were pooled in a random-effects meta-analysis in Revman 5.3. For each outcome, we included subgroups relating to study type (individual, family or school-level and universal or targeted in approach). The quality of evidence was assessed using the GRADE approach. Results: We identified 34 680 titles, screened 27 691 articles and included seventy studies. We found moderate quality evidence indicating that universal school-level interventions were beneficial in relation to tobacco use (odds ratio [OR] 0.77, 95% confidence interval [CI] 0.60–0.97, n=15 354, I 2 57%), alcohol use (OR 0.72, 95% CI 0.56 to 0.92, n=8, 751, I 2 58%), and physical activity (OR 1.32, 95% CI 1.16 to 1.50, n=6 441, I 2 0%) compared to a comparator. Lower quality evidence indicated possible benefit for drug use (OR 0.74, 95% CI 0.55 to 1.00, n=11 058, I 2 69%) and antisocial behaviour (OR 0.81, 95% CI 0.66 to 0.98, n=20 756, I 2 66%), while findings were less certain for sexual risk behaviour (OR 0.80, 95% CI 0.60 to 1.08, n=13 351, I 2 80%; low quality evidence) and unhealthy diet (OR 0.82, 95% CI 0.64 to 1.06, n=6441, I 2 49%, moderate quality evidence). Analyses indicated that family- and individual-level interventions probably have little or no effect on these outcomes, although fewer such studies were identified. The quality of studies was judged to be of moderate or low quality for most outcomes, primarily owing to concerns around selection, performance and detection bias, and heterogeneity between studies. Conclusion: Available evidence is strongest for universal school-level interventions that target multiple risk behaviours demonstrating that they may be effective in preventing certain risk behaviours. However, concerns around poor reporting and study quality highlight the need to strengthen the evidence base in this field. This abstract is based on preliminary findings from a Cochrane review currently underway. Upon completion and approval, the final version is expected to be published in the Cochrane Database of Systematic Reviews.